A DWI-based hypoxia model shows robustness in an external prostatectomy cohort - Fernandez Salamanca, M.; Hompland, T.; Deręgowska-Cylke, M.; Van der Poel, H.; Bekers, E.; Guimaraes, M. A. S.; Lyng, H.; Van der Heide, U. A.; Schoots, I. G.; Van Houdt, P. J. (Frontiers in Oncology, 2024)
Introduction: Prostate cancer hypoxia is a negative prognostic biomarker. A promising MRIbased tool to assess hypoxia is the 'Consumption and Supply based Hypoxia' (CSH) model based on diffusion-weighted imaging (DWI). The aim of the study was to validate the association between the CSH hypoxia fraction (HFDWI) with pathological Grade Group (pGG) and pathological T-staging (pTstage) in an external prostatectomy cohort. Methods: Apparent diffusion coefficient (ADC) and fractional blood volume (fBV) maps were assessed from DWI data from 291 prostatectomies and combined by the CSH model. HFDWI was calculated for each lesion after median scaling of ADC and fBV to address differences in acquisition and analysis between centers. The absolute HFDWI values and the associations of HFDWI between pGG  3 versus  3, and pTstage = 2 versus = 3 in the Netherlands Cancer Institute (NKI) cohort were compared to the obtained by original cohort (Oslo cohort). Statistical T-and Mann-Whitney tests (p<0.05) were performed. Pearson correlation was determined between HFDWI and individual pGG groups. Results The HFDWI showed comparable absolute values and similar metric performance as in the original published cohort. Higher HFDWI values were observed for higher pGG (Oslo: 0.27; NKI: 0.24) compared to lower pGG (Oslo: 0.11; NKI: 0.17). Similar results were obtained for pTstage. Furthermore, HFDWI demonstrated a significant positive correlation with pGG groups 1-5 ( = 0.41, p<0.001). Conclusion: The CSH model exhibited sufficient robustness in the external cohort, suggesting a plausible reflection of true hypoxia and enabling the use of the HFDWI metric for further research into prostate cancer and hypoxia.